Front Matter (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
Editors' Message Inner Work: Teaching and Learning (from) Within ”There lives the dearest freshness deep down things,” Gerald Manley Hopkins writes in God’s Grandeur, capturing in this line, as he sought to reveal through the marvelously unique sounds and rhythms of his poetry, the “inscape” or the unique inner essence of all natural things. “The dearest freshness deep down things” is also Parker Palmer’s focus in The Courage to Teach, where he argues for a teacher’s and a learner’s inner work: exploring “the inner landscape of the teaching self” because “[t]he more familiar we are with our inner terrain, the more surefooted our teaching—and living—becomes” (4,5). As Hopkins—the Victorian poet, Jesuit priest, and keen natural observer—sought to create language and language forms that manifested an object’s inscape, so does Palmer—the Quaker educator—invite us to chart our inner landscape, our inscape, so that our teaching and learning become a “mirror to the soul” (2). The seven essays in the eleventh volume of JAEPL celebrate the richness and diversity of the teacher’s and the student’s inner work. Palmer notes that our inner landscape is interlaced with intellectual, emotional, and spiritual paths, all of which are essential to our inner work. The intellectual path consists of “the form and content of our concepts of how people know and learn”; the emotional path is “how we feel as we teach and learn”; and the spiritual path is carved by the “diverse ways we answer the heart’s longing to be connected with the largeness of life” (4-5). Implicit in The Courage to Teach is a fourth path, a corporeal one. As Hopkins emphasizes, inscape, the site of our inner work, is not separate from the body; it is complicit with our embodied existence. The intellectual, emotional, spiritual, and corporeal fuse in our inner terrain. The essays in Inner Work: Teaching and Learning (from) Within chart each of these paths. We begin with Kami Day who, in We Learn More Than Just Writing, maps a spiritual path in her students’ inner landscape. Although fearing emotional connections with others, Day emphasizes the necessity of such connections for a spiritually rich life and pedagogy. Drawing on Parker Palmer’s formation principles, Day narrates the transformation of her pedagogy when she focuses on “the need for connection, the need to be heard and to listen deeply, the need to teach who I am and be who I am.” She describes a classroom strategy derived from a Quaker Clearness Committee that helps her writing students develop their own “inner writing teachers” in ways that facilitate their inner work through co-authorship. Approaches such as these, Day tells us, enable her to grow spiritually in her professional and her personal life. Gina DeBlase in ‘I Have a New Understanding’: Critical Narrative Inquiry as Transformation in the English-History Classroom carefully tracks the textual traces of a student’s intellectual inner work. Focusing on a case study from a larger ethnography of an interdisciplinary high school literature and history class, DeBlase explores the ways in which Kris, a student in the class, transformed her thinking and, in her own words, “changed my life.” Core to that transformation was narrative thinking deliberately fostered by the class, a fusion of empathy and critical thinking that “merge[d] the boundary of what is with those of what can be in our world.” By engaging in a “feeling/thinking dialogue with text and others,” Kris explores her inscape, in the process becoming a “constructed knower who claimed her own voices and [made] the effort to combine her intuitive knowledge with knowledge learned by others.” Emphasizing the crisscross of spiritual, corporeal, intellectual, and emotional paths, Geraldine DeLuca in Headstands, Writing, and the Rhetoric of Radical Self-Acceptance underscores the necessity of attending to all paths in teaching and learning. Building her essay around the sirsasana, or the headstand in yoga, which becomes both an act of faith and a metaphor for an act of faith, DeLuca suggests that our inner work is at the nexus point of body, mind, and spirit. Here at this crossroads is where we need to foster an ethic of compassion, of acceptance of self and other. We live in a culture, she says, “that accepts as useful the value of everyone feeling not good enough.” The combination of institutional edicts and institutional culture fosters a kind of discursive wildness or “monkey brain” that disrupts any effort at inner work and transforms writing into a scramble for correctness. Without time and space for stillness, without “a holding environment where it is safe to take risk,” neither we nor our students can learn to treat our bodies, our minds, and our writing with dignity. Complementing and extending DeLuca’s insights concerning the nexus point of bodies and minds, Sue Hum in Idioms as Cultural Commonplaces: Corporeal Lessons from Hokkien Idioms highlights a problem in conventional writing pedagogy: its failure to recognize that a teacher’s and student’s inner work involves language, intellect, cultural environments, and bodies. Focusing on Hokkien, a Chinese oral dialect, Hum counters “the Western predisposition of separating mind from body, bracketing the cognitive from the material.” By ignoring these connections, teachers fail to recognize the intellectual and corporeal changes that students, especially those from “working class backgrounds, marginalized ethnicities, and other counties,” must undergo to assimilate into Western literary practices. Bodies as well as minds are required to mimic a middle-class orientation. Hum demonstrates through an exploration of Hokkien idioms how students can be invited to explore those intellectual and corporeal changes by connecting and analyzing the idioms of their home culture, enriching both their own and each other’s literacy practices. Laurence Musgrove in What Happens When We Read seeks to provide teachers and students with a praxis that makes our students’ intellectual and emotional inner work visible. He is specifically interested in the challenges posed by reading, a process even more invisible than writing. Encouraging students to forge a “developing and active relationship between themselves and the objects of their study,” Musgrove invites students to create visual depictions of their reading. He models that activity by offering students his own image of responsive, reflective, responsible reading. That figure serves as the focus of his essay as he explores the four interconnective elements of reading: the text, the reader, the response, and the review. With this image of reading as a reference point, Musgrove argues that his students are better able to become “mature readers of themselves and of the texts offered to them.” Attending to the emotional and intellectual paths crisscrossing our inner terrain, Alexandria Peary in Mindfulness, Buddhism, and the Rogerian Argument sees empathy as both the problem and the solution to successful creation of Rogerian arguments. Rogerian argument is important because it offers a “therapeutic, humanistic approach to argument,” but it poses challenges for students who “must be able to visualize imaginatively that which is distinct from their current outlook” before they can communicate via Rogerian argument. The development of that “rhetorical imagination” is difficult, but it can be nurtured by experiences with the Buddhist practices of deep listening and mindfulness. Peary describes two practices she incorporates into her undergraduate composition classroom: mindful speech and loving-kindness meditation. When these practices become integral to their thinking, students become “people blessed with imagination,” ready to engage in humane rather than adversarial argument. We conclude with Stan Scott’s Poetry and the Art of Meditation: Going behind the Symbols, which returns us by a circuitous path to poetry and inner work. “Can poetry guide readers to spiritual experience,” Scott asks, and answers that the Benedictine practice of lectio divina, or sacred reading, can be a bridge to spiritual experience, especially when the object of contemplation is poetry centered on the mystical. Sacred reading is a meditative stance in which the reader commits complete attention to the text. By surrendering to the text, especially the poetic text which makes unusual demands on attention, readers are present with the text. Such a centering “sets us on a course of removing fear and so restoring our vital relations to Spirit.” Scott then illustrates lectio divina by a richly textured reading of poetic texts that evoke spiritual experiences and development. Engaging in sacred reading, Scott concludes, helps our students act “with greater responsibility toward what is authentic in themselves and others.” Contemplating and experiencing an object’s inscape drove Hopkins’ poetry and balanced him between his spiritual faith and his passionate appreciation for the “pied beauty” of the natural world. Wedded to his keen naturalistic eye and infused with his spiritual calling, inscape served as the site of his inner work. As both teachers and learners, we too are called to commit ourselves to inner work, to an exploration and a charting of inscape that will foster excellence in teaching and learning. As Palmer reminds us, “the most practical thing we can achieve in any kind of work is insight into what is happening inside us as we do it” (5). The essays in this volume of JAEPL provide a map, a Beidecker, to just such an endeavor. Works Cited Hopkins, Gerard Manley. God’s Grandeur.The Poems of Gerald Manley Hopkins (1918). 22 Aug. 2005. http://www.dundee.ac.uk/english/wics/gmh/framconc.htm. —. Pied Beauty.The Poems of Gerald Manley Hopkins (1918). 22 Aug. 2005. http://www.dundee.ac.uk/english/wics/gmh/framconc.htm. Palmer, Parker. The Courage to Teach: Exploring the Inner Landscape of a Teacher’s Life. San Francisco: Jossey-Bass, 1998.